Simulation Analysis of the Temperature Field and Thermal Deformation of Wind Turbine High Level Gear - Chen Changzheng; Hao Renqiang; Liu Jie; Zhao Xin (Jixie chuandong)
In order to study the high speed wind turbine stage gear thermal deformation,the parametric finite element model of the gear is established based on the APDL language of ANSYS.The finite element model boundary conditions and loads are calculated according to the theories of tribology,heat transfer and meshing.The single gear steady-state temperature field distribution is obtained.The temperature change with power and rotating speed are analyzed systematically.The influence of ambient temperature and friction coefficient on wind turbine gear temperature is investigated.The gear heat-structure coupling field is analyzed.Add the steady state thermal analysis results as the load to the structure of the field,the gear thermal deformation is calculated,and a theoretical basis for the gear modification is provided.